Motivational Factors on the Use of Mobile Food Delivery Services in Lapu-Lapu City, Cebu, Philippines - JAMES GARCIA ESGUERRA; Analiza A. Payao; Nena M. Capitan; Vanessa Sofia Caballes; Mary Joy Queriado; Chennie Pearl Razon; Ma. Theres Cañete; Cathleen Claire Dagatan Dagatan (International Journal of Business Studies, 2023)
The study investigates the motivational factors that influence customers on the use of mobile food delivery services. The study utilized a descriptive method to describe the factors that influence customers to use the mobile food application. A total of 100 response was garnered by the study. In addition to the survey, the study also presented the ASEAN development on the use of the application, it was observed that this emerging business model contributed to the gross merchandise value. In the context of the Philippines, it was found that it is already a growing business model that provided an avenue for the food and beverage industry to thrive during the pandemic. The results of the survey also showed that the identified factors were very influential in the decision of the customers to use the application. Further study is recommended using other indicators and approaches to have a better understanding of the use of mobile food delivery applications.